A review on the current research on graphene-based aerogels and their applications. (July 2021) - Nassar, Gaelle; Daou, Elissa; Najjar, Rita; Bassil, Maria; Habchi, Roland
Highlights: Using graphene oxide in the synthesis of graphene aerogels (GAs). Methods include: chemical and hydrothermal reduction, polymerization, and 3D printing. Energy storage and supercapacitors are widely used applications. Electrodes, oil absorption, and water treatment are currently in high demand. Abstract: Graphene aerogels (GAs) are amongst the lightest materials in the world. They attracted increasing interest in academia and industry because of their exceptional and unique properties, like high mechanical strength, electrical conductivity, thermal resistance, and adsorption capacity. In this review, we describe advances in research and development of a variety of methods that lead to the synthesis of graphene-based aerogels. First, the main common methods for producing GAs are examined, such as chemical reduction, hydrothermal reduction, crosslinking, polymerization methods, and template-directed reduction. Furthermore, the advancement of the 3D printing of GAs is presented. These methods resulted in GAs with porous hierarchical textures, low densities, and improved electrical conductivities, robust mechanical properties, better stability, and excellent adsorption potential. Then, the promising potential applications of GAs in the domains of energy storage, energy conversion, and environmental protection are evaluated. Finally, the prospects and challenges associated with the manufacturing of GAs are discussed.